Pengaruh Probiotik Dan Trichorderma Terhadap Hara Pupuk Kandang Yang Berasal Dari Feses Sapi Dan Kambing - S, Suhesy; A, Adriani (Fakultas Peternakan Universitas Jambi, 2014)
The aim of this study was to investigate the best standard procedure to produce a good nutrient bio-fertilizer from with the basic ingredient cow and goat faeces and probiotic and Trichoderma. The design of this experiment was Completely Randomized Design in factorial arrangement (3x3x4) with the factor A, the animal feces, and the factor B, probiotic and Trichoderma, and four replications. For factor A, there were 100% goat feces, 50% cow feces and 50% goat feces + 50% cow feces for A1, A2 and A3 respectively and for factors B there were 5% probiotic, 5% Tricoderma and 2.5% probiotic + 2.5% Tricoderma for B1, B2 and B3 respectively. Parameters measured were pH, the content of N, P, K and C/N ratio. Results of this experiment showed that the fertilizer originated from goat feces consisted of more nutrient than those from cow feces. The mix of both probiotic and Trichoderma was the good activator in producing biofertilizer. The average content of P was 0.68% with the range of 0.39 – 0.96%. The average content of K was 1.97% with the range of 0.60 – 1.78%. The average content of C was 19.51% with the range of 13.53 – 27.07%. The ratio of C/N was 11.89 with the range of 8.54 – 18.22. It could be concluded that the best chemical composition in this study was fertilizer originated from goat feces mixed with probiotic and Trichoderma as activator.